Analisis Faktor Rendahnya Pemahaman Siswa tentang Kerusakan Lingkungan di Sekolah Dasar Negeri 12 Padang Koto Gadang - M. Farel Rezkia Sonra; Ari Suriani (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This research investigates the factors contributing to low understanding of environmental degradation among sixth-grade students at SDN 12 Padang Koto Gadang. The study aims to identify internal and external factors affecting students' comprehension of environmental issues within the IPAS (Natural and Social Sciences) curriculum. Using a qualitative descriptive approach, data were collected through in-depth interviews with the class teacher, classroom observations, and document analysis of lesson plans and student assessment records. The findings reveal that internal factors include low learning motivation, where students perceive environmental materials as mere memorization tasks, and a significant mismatch between students' kinesthetic-visual learning styles (78%) and the predominantly auditory-lecture teaching methods. External factors encompass conventional teaching approaches dominating 85% of classroom time, limited technological infrastructure, and insufficient interactive learning resources. A paradoxical finding shows that while 70% of students claim environmental concern, only 23% consistently practice eco-friendly behaviors, indicating a substantial gap between cognitive knowledge and behavioral application. The study recommends implementing a hybrid learning model combining Problem-Based Learning with local contexts, utilizing simple nature-based media, and establishing strategic community partnerships. These findings contribute to developing more adaptive and contextual teaching methods aligned with Merdeka Curriculum principles for elementary environmental education.